2014
DOI: 10.3109/08039488.2014.949305
|View full text |Cite
|
Sign up to set email alerts
|

Eating Disorder Inventory-3, validation in Swedish patients with eating disorders, psychiatric outpatients and a normal control sample

Abstract: The reliability was acceptable for all subscales except Asceticism among normal controls. Analysis of variance showed that the EDI-3 discriminates significantly between eating disorders and normal controls. Anorexia nervosa was significantly discriminated from bulimia nervosa and eating disorder not otherwise specified on the Eating Disorder Risk Scales. Swedish patients scored significantly lower than patients from other countries on the majority of the subscales. Drive for Thinness is the second best predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 21 publications
4
39
0
Order By: Relevance
“…Higher scores on each scale indicate greater frequency of symptom like behaviour. The reliability and validity of the EDI-3 (and its earlier version EDI-2) is well documented (Brewin, Baggott, Dugard, & Arcelus, 2014;Clausen et al, 2011;Garner, 2004;Nevonen et al, 2006;Nyman-Carlsson, Engstrom, Norring, & Nevonen, 2015). The current sample size (39) to item ratio (7-9 items) is marginally acceptable for internal reliability analysis.…”
Section: Methodsmentioning
confidence: 95%
“…Higher scores on each scale indicate greater frequency of symptom like behaviour. The reliability and validity of the EDI-3 (and its earlier version EDI-2) is well documented (Brewin, Baggott, Dugard, & Arcelus, 2014;Clausen et al, 2011;Garner, 2004;Nevonen et al, 2006;Nyman-Carlsson, Engstrom, Norring, & Nevonen, 2015). The current sample size (39) to item ratio (7-9 items) is marginally acceptable for internal reliability analysis.…”
Section: Methodsmentioning
confidence: 95%
“…While Swedish controls scored higher on interoceptive deficits, emotional dysregulation and maturity fears, the international counterpart achieved higher score on interpersonal alienation subscale (13). Also, Nyman-Carlsson et al reported that psychiatric outpatients scored higher than both ED and normal to controls just in two scales, including interpersonal insecurity and interpersonal alienation (13). Furthermore, a study released by Waldherr et al, showed that the average EDI scores of the southern countries are similar to the North American and tendency to weight seems to be less prevalent in the Netherlands than in North America and central and southern parts of Europe.…”
Section: Discussionmentioning
confidence: 99%
“…However, it could be said that the Stanford et al study participants were 66 men who received treatment for eating disorder and addiction and 45 healthy ones were matched as control group (6). The comparison between Swedish, Danish and international control samples demonstrated that the Swedish control scored notably higher than the other two controls, unless in the eating disorder risk scales, perfectionism and asceticism (13). While Swedish controls scored higher on interoceptive deficits, emotional dysregulation and maturity fears, the international counterpart achieved higher score on interpersonal alienation subscale (13).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations